PROBLEMATIKA PEMBELAJARAN DARING MAHARATUL QIRAAH PADA JURUSAN SASTRA ARAB UMI (Karya Ilmiah Mahasiswa (KIMA), 2022)
This research aims to find out the problems of maharatul qiraah online learning in UMI Arabic literature, and to find out the supporting and inhibitory factors in online learning of maharatul qiraah in UMI Arabic literature. The method used in this research is the qualitative method. Data collection techniques in this study are observation, interview, and documentation. Data analysis techniques in this study are data retrieval, data reduction, data presentation, and conclusion/verification. The result of this study is the problem of online learning maharatul qiraah disastra Arab UMI that is during the teaching and learning process some students have difficulty in understanding the content of the material from lecturers, ineffective learning due to a less stable network, then the supporting factor is the availability of gadgets, stable networks and student worksheet books, the inhibitory factor is a less stable network so that learning is ineffective. a. the problem of online learning is that (1) students cannot access Zoom Meeting without internet quota. (2) Zoom Meeting application cannot be accessed if the internet network is stable. (3) Difficulty in understanding the content of the material. (4) Feeling bored and tired. b. supporting factors are (1) the availability of devices. (2) quota and stable internet network. (3) Student worksheet book. b. inhibitory factors are (1) students are less active in learning, 2) time constraints on zoom meeting applications, (3) unstable networks so that learning is ineffective, (4) lack of basic knowledge of Arabic.